Spatio-temporal variability in soil CO2 efflux and regulatory physicochemical parameters from the tropical urban natural and anthropogenic land use classes. (1st October 2021) - Upadhyay, Shweta; Singh, Rishikesh; Verma, Pramit; Raghubanshi, Akhilesh Singh
Abstract: Urban ecosystems, the heterogeneous and rapidly changing landscape, showed a considerable impact on the global C cycle. However, studies encompassing the spatial differences in urban land uses on soil C dynamics are limited in tropical ecosystems. In this study, seasonal and temporal variability in soil CO2 efflux (SCE) and its regulatory physicochemical variables under five urban land use classes viz., Bare (BAR), Agriculture (AGR), Plantation (PLT), Grassland (GRA) and Lawns (LAW) were assessed from 2014 to 2016. Bare land use was considered as the reference for observing the variation for different land uses. Seasonal measurements of SCE, soil temperature, moisture content, pH, ammonium-N, nitrate-N and microbial biomass C (MBC) were performed whereas soil organic C (SOC), soil N, and soil physical properties were measured annually. Our results showed a significant ( P < 0.01) increase in SCE by 89%, 117%, 132% and 166% for land use types from BAR to AGR, PLT, GRA and LAW, respectively. The results revealed a two-fold increase in SCE from anthropogenically managed urban lawns as compared to bare soil. PLT and LAW land use classes showed higher SOC and N contents. SCE was found positively correlated with temperature, moisture, SOC, soil N and MBC whereas negatively correlated with ammonium-N and nitrate-N (at P < 0.05) for the overall dataset. Soil moisture, temperature, SOC, porosity and pH were identified as the major determinant of urban SCE by explaining 63% of the variability in overall SCE. Further, temperature for BAR and LAW; moisture for PLT; ammonium-N for GRA; and nitrate-N for AGR were identified as the major regulators of SCE for different land use classes. The findings revealed that the interaction of soil temperature and moisture with nutrient availability regulates overall and seasonal variability in SCE in an urban ecosystem. Since these variables are highly affected by climate change, thus, the soil C source-sink relationships in tropical urban ecosystems may further change and induce a positive global warming potential from urban ecosystems. Graphical abstract: Image 1 Highlights: Urban lawns showed 166% higher soil CO2 efflux (SCE) as compared to bare soil. Plantation showed higher soil organic C and available nutrients whereas lower SCE. Strong seasonality observed in SCE with higher value during rainy and lower during winter. Soil moisture and temperature showed positive whereas nutrient availability showed negative control on the SCE. Urban lawns showed higher potential for C accumulation with proper management.